2019
DOI: 10.1016/j.fertnstert.2018.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Differential gene expression during placentation in pregnancies conceived with different fertility treatments compared with spontaneous pregnancies

Abstract: Objective: To identify differences in the transcriptomic profiles during placentation from pregnancies conceived spontaneously to those with infertility, using non-in vitro fertilization (NIFT) or in vitro fertilization (IVF).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 88 publications
(86 reference statements)
0
6
0
Order By: Relevance
“…Placentation may be altered due to the supraphysiological blood concentrations of oestradiol and progesterone following ovarian stimulation and fresh ET, lasting at least through the first trimester (Järvelä et al, 2014) and possibly causing increased risk of low birth weight (Pereira et al, 2017). Varying epigenetic changes and differences in gene expression in placentas and children from pregnancies originating after FET, fresh ET and NC have been discovered (Estill et al, 2016;Choux et al, 2018;Lee et al, 2019). It has also been suggested that the effect of ART on DNA methylation in placenta is genotype specific (Marjonen et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Placentation may be altered due to the supraphysiological blood concentrations of oestradiol and progesterone following ovarian stimulation and fresh ET, lasting at least through the first trimester (Järvelä et al, 2014) and possibly causing increased risk of low birth weight (Pereira et al, 2017). Varying epigenetic changes and differences in gene expression in placentas and children from pregnancies originating after FET, fresh ET and NC have been discovered (Estill et al, 2016;Choux et al, 2018;Lee et al, 2019). It has also been suggested that the effect of ART on DNA methylation in placenta is genotype specific (Marjonen et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…A second study investigated first-trimester samples from chorionic villus sampling and included a non-IVF fertility treatment group in addition to the IVF and SC groups. Herein the authors reported modest differences in the transcriptome and suggested that underlying infertility, in addition to treatment-related factors, might be key contributors to the observed gene expression abnormalities in the IVF group ( Lee et al, 2019 ). Similarly, a recent study that compared first-trimester maternal plasma metabolomic profiles in women undergoing IVF, non-IVF fertility treatment, and SC ( Sun et al, 2019 ) found elevated circulating levels of several lipid and lipid-related components (e.g., steroid metabolites, and lipids with docosahexaenoyl acyl chains, and acylcholines) in the infertile groups of women, especially when IVF was performed.…”
Section: Intrauterine Mechanisms–placental Programming In Artmentioning
confidence: 90%
“…However, several studies (34)(35)(36) supported that the alternation of epigenetics in the process of FET was linked with abnormal placentation and fetal growth. In addition, differences in gene expression were detected in placentas and fetuses from FET cycles (37). Owing to the limited sample size and multiple potential factors during pregnancy, further researches are needed to address these changes.…”
Section: Comparison With Other Studiesmentioning
confidence: 99%